Iran J Pathol 2018
DOI: 10.30699/ijp.13.2.212
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation Between Serum Vitamin D Level and Total Antioxidant Capacity in diabetic and Non-diabetic Subjects in Iran

Abstract: Background & objective: Increase in intra-and extracellular glucose levels can cause oxidative stress, and theprolonged imbalance between prooxidants and antioxidantscan lead to cell damage and the associated complications in patients with diabetes. Vitamin D acts as a strong antioxidant in the body and several studies emphasized on its important role to preventoxidative stress in prediabeticand diabetic subjects. The current study aimed at determining and comparingthe total antioxidant capacity (TAC) in indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…[37] Similarly Aoucheri et al, Zare-Mirzaie et al, and Dhas et al, reported relatively lower values. [38,39,40] Sheth et al reported values of 8.36% ± 1.79%, which were comparable to those of the current study. [41] Previous study stated that a FBS of patients was 175.5 ± 30.08 (mg/dL) which is significantly higher than control group their mean 74.17 ± 13.76 (mg/dL) (P< 0.01).…”
Section: Table;5supporting
confidence: 91%
“…[37] Similarly Aoucheri et al, Zare-Mirzaie et al, and Dhas et al, reported relatively lower values. [38,39,40] Sheth et al reported values of 8.36% ± 1.79%, which were comparable to those of the current study. [41] Previous study stated that a FBS of patients was 175.5 ± 30.08 (mg/dL) which is significantly higher than control group their mean 74.17 ± 13.76 (mg/dL) (P< 0.01).…”
Section: Table;5supporting
confidence: 91%
“…Our study showed that people with high BMI and severe VIT D3 de ciency have higher HSCRP than other group when adjusted with age, in people younger than 60 year old; decrease in VITD3 level accompanied by high HSCRP whereas in people older than 60 year, this relation is reverse. Data from latter studies (17,18,19) are very con icting, This nding may be due to some other interfering factor such as in ammatory markers. Difference between results of our study and others may be due to different study population.…”
Section: Discussionmentioning
confidence: 95%
“…In AMI, the serum level of TOS is correlated with the intensity and complexity of coronary artery disease [59]. It was suggested that TAC may represent an indicator of the protective effects of antioxidant agents, and it is used as a new biomarker for the prevention, diagnosis, and prognosis of DM and several other diseases [60]. TAC was reported to be low in patients with AMI; therefore, the antioxidant therapy may have beneficial effects in the prevention of coronary artery disease [61] Thiols are an important antioxidant system since they are able to mediate redox-signaling processes as a response to oxidative stress, playing a significant role in mitigating the lipid peroxidative effects of ROS, along with other antioxidants in the body [62,63].…”
Section: Discussionmentioning
confidence: 99%